Induction of lily (Lilium sp.) bulblets from scales, using auxins and cytokinins - Vera, Miguel (2020)
The objective of this investigation was to induce lily bulblets (Lilium sp.) from scales using growth regulators. In the induction stage of bulblets, two caliber bulbs were used, also 100 mg/L of naphthaleneacetic acid (NAA), 50 and 100 mg/L of benzylaminopurine (BAP), alone or in combination. The bulbs were disinfected and subjected to the growth regulators, and the scales placed in PREMIX substrate at field capacity. In the establishment stage, induced bulbs were used and placed in a substrate for the growth and development of seedlings. The results showed that the use of 100 mg/L NAA, 100 mg/L of BAP, alone or in combination, allowed to induce a greater number of bulblets from bulbs of larger caliber compared to the control. In the establishment stage it was determined that the bulblets induced from larger caliber bulb scales and subjected to concentrations of 100 mg/L of NAA + 50 mg/L of BAP, the seedlings showed greater leaf length compared to scales without the use of growth regulators. It was possible to develop a bulb induction protocol in lily scales to obtain pre-basic seed.